2011
DOI: 10.5194/hess-15-1945-2011
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying spatial and temporal discharge dynamics of an event in a first order stream, using distributed temperature sensing

Abstract: Abstract. Understanding the spatial distribution of discharge can be important for water quality and quantity modeling. Non-steady flood waves can, particularly as a result of short high intensity summer rainstorms, influence small headwater streams significantly. The aim of this paper is to quantify the spatial and temporal dynamics of stream flow in a headwater stream during a summer rainstorm. These dynamics include gains and losses of stream water, the effect of bypasses that become active and hyporheic ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 49 publications
3
23
0
Order By: Relevance
“…Thus, the evaluation statistics compared favourably to those observed in previous studies using similar models (e.g. Westhoff et al, 2011). The model was biased towards slight overprediction (as indicated by percent bias), but in all cases this was < 2.0 %.…”
Section: Modelled Spatio-temporal Water Temperature Patternssupporting
confidence: 69%
See 1 more Smart Citation
“…Thus, the evaluation statistics compared favourably to those observed in previous studies using similar models (e.g. Westhoff et al, 2011). The model was biased towards slight overprediction (as indicated by percent bias), but in all cases this was < 2.0 %.…”
Section: Modelled Spatio-temporal Water Temperature Patternssupporting
confidence: 69%
“…Several studies have documented daytime cooling gradients (instantaneous decreases in downstream temperature) under forest canopies located downstream of open (no trees) land use, although the magnitude of reported cooling effects varied between studies (e.g. Brown et al, 1971;Rutherford et al, 1997;McGurck, 1989;Keith et al, 1998;Zwieniecki and Newton, 1999;Torgerson et al, 1999;Story et al, 2003;Westhoff et al, 2011). For example, McGurck (1989), Keith et al (1998) and Story et al (2003) observed gradients of between 4.0 and 9.2 ‱ C km −1 .…”
mentioning
confidence: 99%
“…Brown et al, 1971;Rutherford et al, 1997;McGurck, 1989;Keith et al, 1998;Zwieniecki and Newton, 1999;Torgerson et al, 1999;Story et al, 2003;Westhoff et al, 2011). For example, McGurck (1989), Keith et al (1998) and Story et al (2003) observed gradients of between 4.0 and 9.2 ‱ C km −1 .…”
Section: G Garner Et Al: What Causes Cooling Water Temperature Gradmentioning
confidence: 98%
“…In rivers, temperature exerts an important control on physiochemical characteristics of water [15] and it is a driver of Water 2017, 9, 358 2 of 16 numerous biological processes, controlling the structure of ecological communities and habitat complexity [16,17]. Approaches for measuring stream water temperature cover a wide range of methods including temperature loggers and thermometers [18][19][20], fiber-optic distributed temperature sensing (FO-DTS) [21,22] and thermal infrared (TIR) cameras [23][24][25].…”
Section: Introductionmentioning
confidence: 99%